On the problem of the influence of the magnetosphere disturbance onto the rotational regime of the Earth - V.Yu. Belashov; I.A. Nasyrov; R.S. Gordeev (Учёные записки Казанского университета: Серия Физико-математические науки)
The earlier hypothesis on solar control (through changes of global magnetic disturbance in the magnetosphere) of the Earth rotational regime has been confirmed on the basis of the analysis of heliogeophysical data for the period of 1927 to 2017. It has been shown that the stream of solar plasma (solar wind), which is variable on its characteristics, transfers a part of its energy to the magnetosphere while interacting with it. This energy, along with the energy, which is accumulated due to the unipolar induction phenomenon in the magnetosphere tail and released from time to time, causes changes in the angular velocity of rotation of the Earth based on the effect of the inverted MHD-generator of alternating current. It has been confirmed that the earlier offered mechanism of interaction between the external magnetic field and the constant field connected rigidly with the Earth is energetically significant. The fluctuations of day duration correlate well with changes in the solar activity and global magnetosphere disturbance both in 11-year and in annual and semiannual cycles; the steady negative correlation has been observed between changes in the day duration and the monthly sums of polarities of the sectors of the interplanetary magnetic field. Possible ways of experimental confirmation of the obtained results have been discussed.